2021
DOI: 10.1364/prj.439849
|View full text |Cite
|
Sign up to set email alerts
|

Sculpturing spatiotemporal wavepackets with chirped pulses

Abstract: Pulse shaping has become a powerful tool in generating complicated ultrafast optical waveforms to meet specific application needs. Traditionally, pulse shaping focuses on the temporal waveform synthesis. Recent interests in structuring light in the spatiotemporal domain rely on Fourier analysis. A space-to-time mapping technique allows us to directly imprint complex spatiotemporal modulation through taking advantage of the relationship between frequency and time of chirped pulses. The concept is experimentally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…However, this concept lay dormant until experiments by Milchberg et al uncovered that such STOVs occur during the nonlinear pulse collapse dynamics in self-focusing media [61]. Subsequently, it was recognized that STOVs can in fact be synthesized linearly [62,63], and the concept has since attracted considerable attention [388][389][390][391][392]. It is important to note that the axis of the OAM points in the š‘¦ direction rather than along š‘§ as in conventional OAM beams, and such a STOV is thus said to exhibit transverse OAM.…”
Section: St Optical Vorticesmentioning
confidence: 99%
“…However, this concept lay dormant until experiments by Milchberg et al uncovered that such STOVs occur during the nonlinear pulse collapse dynamics in self-focusing media [61]. Subsequently, it was recognized that STOVs can in fact be synthesized linearly [62,63], and the concept has since attracted considerable attention [388][389][390][391][392]. It is important to note that the axis of the OAM points in the š‘¦ direction rather than along š‘§ as in conventional OAM beams, and such a STOV is thus said to exhibit transverse OAM.…”
Section: St Optical Vorticesmentioning
confidence: 99%
“…Recently, kinds of spatiotemporal coupling methods are widely used to control the propagation or structure of Bessel wave-packets 24 ā€“ 28 , spaceā€“time wave-packets 29 ā€“ 38 , flying focuses 39 ā€“ 42 , spatiotemporal optical vortices 43 ā€“ 45 , etc. In our previous works, we have proposed a method to control the group-velocity and group-acceleration of the propagation-invariant optical wave-packet generated by the conical superposition by separating the pulse-front from the phase-front and shaping the pulse-front from a plane into an arbitrarily-axisymmetric distribution, and in simulation superluminal or luminal or subluminal group-velocities, accelerating or uniform-motion or decelerating group-accelerations, and even nearly-programmable group-velocities in a single propagating path have been introduced 46 , 47 .…”
Section: Introductionmentioning
confidence: 99%
“…Next, we further investigate how this SRSI method can be used to characterize the dispersion of ST-OAM pulses. Former studies have shown that dispersion can significantly reshape the spatiotemporal profile of ST-OAM pulses, , although the spectral intensity remains unchanged. ST-OAM pulses can acquire dispersion (i.e., chirp) as the beam propagates through optical elements such as lenses, beam splitters, filters, and so forth.…”
Section: Resultsmentioning
confidence: 99%